2015
DOI: 10.2208/journalofjsce.3.1_60
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Radioactive Tracer Transport Using Isorsm and Uncertainty Analyses

Abstract: Due to the massive earthquakes and tsunami on March 11th, 2011 in Eastern Japan, Fukushima Daiichi nuclear power plant was severely damaged and some reactors were exploded. Then radioactive particles were widely spread out. In this study, we modified the stable isotope module of RSM (IsoRSM, Yoshimura et al.) to enable to simulate the transport of the radioactive tracers, namely iodine 131 and cesium 137, by including the dry and wet deposition processes. The control experiment with 10km resolution and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The wet deposition (washout process) is calculated as: where C is the atmospheric concentration of radioactive materials; α is the washout coefficient (0.5); and P and q are the water condensation and the water vapour at each atmospheric layer, respectively 30 .…”
Section: Methodsmentioning
confidence: 99%
“…The wet deposition (washout process) is calculated as: where C is the atmospheric concentration of radioactive materials; α is the washout coefficient (0.5); and P and q are the water condensation and the water vapour at each atmospheric layer, respectively 30 .…”
Section: Methodsmentioning
confidence: 99%
“…where C is atmospheric concentration of radioactive materials, α is the washout coefficient (0.5), and P and q are the vertically integrated water condensation and the water vapour in the atmospheric column, respectively36.…”
Section: Methodsmentioning
confidence: 99%
“…For the results reported herein, we used a version of IsoRSM in which aerosol forms of 131 I and 137 Cs and their deposition processes were implemented by Saya et al (). Yoshikane et al () showed that the radioactive material version of IsoRSM was reasonably skilled at simulating radioactive materials produced in the Fukushima accident.…”
Section: Methodsmentioning
confidence: 99%
“…The following equation developed by Saya et al () was applied as the wet deposition process. The wet deposition process can be separated into two types, rainout and wash out, depending on when materials are incorporated into precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation